Multivariate analysis of soils irrigated with aquaculture wastewater - Leal-Mendoza, Aldo Iram (2022)
Introduction. Aquaculture wastewater is an important resource that can be used for irrigation of agricultural land. Objective. To evaluate the physical, chemical, and biological properties of soils with continuous irrigation of aquaculture wastewater and to identify the variables that provide more information in regarding their behavior under irrigation. Materials and methods. The treatments were three agricultural soils, located in the south of the state of Tlaxcala, Mexico, in 2018 soil sampling was performed at a depth of 0-30 cm and nine replicates to determine: pH, organic matter, electrical conductivity, nitrate, ammonium, total N, phosphorus, potassium, calcium, magnesium, texture, apparent density, and microbial activity, with which a principal component analysis (PCA) was applied. Results. Irrigation with aquaculture wastewater increased the concentration of phosphorus, potassium, calcium, ammonium, and nitrates. Through linear correlation analysis and PCA, it was obtained that the first principal component explained 76 % of the total variance, associated with pH, organic matter, sand, total N, potassium, magnesium, and ammonium, while the second component explained 23 % of the total variance, linked to phosphorus and adsorption by the exchange complex provided by the clay. Conclusion. Irrigation with aquaculture wastewater improved soil fertility and with the principal component analysis (PCA) phosphorus, clay particle, and magnesium were identified as indicator variables that will support the management of soils irrigated with aquaculture wastewater.